VD_FINDINFO Jug / 2022 / 473 vom 1. Februar 2022 - VD Tribunal cantonal (2022)
RÉSILIATION IMMÉDIATE, INDEMNITÉ DE VACANCES, CERTIFICAT DE TRAVAIL, CERTIFICAT MÉDICAL | 337 CO, 16 LPers-VD, 21 LPers-VD, 22 LPers-VD, 23 LPers-VD, 59 LPers-VD, 61 LPers-VD, 64 LPers-VD, 65 LPers-VD, 37 RLPers-VD, 65 RLPers-VD